Degressively proportional apportionment of seats in the European Parliament : from a simple idea to a problematic legal rule - Cegiełka, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The proportional representation of citizens in collegial bodies is today the most frequently applied solution among electoral systems. It assumes an ideal condition with one delegate representing the same number of inhabitants, perceived as the fairest solution. However, in the European Parliament, fairness is seen somewhat differently. Due to the considerable dissimilarity of member states as regards the numbers of their populations, it is assumed as fair that delegates from less populous countries represent more citizens that those from more populous countries. Yet this seemingly uncomplicated idea, soon referred to as degressive proportionality, turned out to be a major problem in practice. This paper presents the story of the efforts to formalize degressive proportionality by members of the European Parliament
Mathematical Economics, 2016, Nr 12 (19), s.15-30
Keywords: degressive proportionality; allocation of seats; European Parliament